OPTIMASI FUZZY ADAPTIF PARTIKEL SWARM PADA PERMASALAHAN RUTE KENDARAAN DENGAN PEMISAHAN PENGIRIMAN - ., Arnita (JURNAL PENELITIAN SAINTIKA, 2014)
This study aims to find the shortest route models and the use ofutilities (vehicles) as little as possible so that costs can be minimized withsplit delivery imposed. Split Delivery Routing Problem (SDVRP) is avariation of the classical VRP, where the assumption of a single visiteliminated and customers can be served by a different vehicle. This studyshow that the cost savings of more than 50% would be obtained if splitdelivery enforced. Parameters used in the simulation using Fuzzy Adaptive Particle Swarm algorithm is NP = 40, T = 300, max = 0, min =0,4, c1 = 2, c2 + c3 = 2 and maximum distance is 400 kilometer. And theresults obtained from simulation is used four vehicles and four route, andminimum distance is 42.3149. After be compared with tabu searchGenreau et al method, FAPSO method can increase 1.84% achievement ofthe best solution. While the tabu search method used Gendreau et al ableto increase 1.62% achievement of the best solution.